Psychological processes in language learning and teaching: Scoping review and future research directions - Dey, Manna (Journal of Psychological Perspective, 2021)
The field of psycholinguistics has produced many hypotheses which explain how a person speaks and understands the language spoken or written. In the area of language, instruction theories have been employed. In designing language education approaches, several professionals adopt them as their fundamental theories. It is called a method of psycholinguistics. The psycholinguistic method considers learning as an individual cognitive process that takes place within the individual and then moves to the social dimension. There are various ways, such as natural method, whole physical response methods, and suggested contemporary method, which are founded on the theory of the psycholinguist. These methods utilise psychological concepts, such as learning your first or second language (second language learning), learning a language (linguistic perception), and language (second language learning). The perception of languages refers to hearing and reading, while the creation of languages refers to speaking and writing. The four language skills are listening, reading, speaking, and writing. In particular, psycholinguistics helps to comprehend the difficulty of both intrinsic and extrinsic problems in these four skills. Psycholinguistics also contributes to explaining the language learning faults of students. In addition, psycholinguistics describes certain types of cerebral illnesses, such as graphics and aphasia, which must be treated appropriately, that influence language development. The use of the suitable approach for teaching these four linguistics teaches mainly psycholinguistic skills.